2010
DOI: 10.1371/journal.pone.0014035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Human Neural Stem Cells in the Ischemic Rat Brain upon Transient Immunosuppression

Abstract: Understanding the physiology of human neural stem cells (hNSCs) in the context of cell therapy for neurodegenerative disorders is of paramount importance, yet large-scale studies are hampered by the slow-expansion rate of these cells. To overcome this issue, we previously established immortal, non-transformed, telencephalic-diencephalic hNSCs (IhNSCs) from the fetal brain. Here, we investigated the fate of these IhNSC's immediate progeny (i.e. neural progenitors; IhNSC-Ps) upon unilateral implantation into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Lee et al 104 reported that the majority of the donor cells remained undifferentiated or became astroglia, with only about 5% and 4% differentiation into neurons and oligodendrocytes, respectively. In an adult ischemic brain injury model, under the condition of immunosuppression either transiently or throughout the experiment, Nodari et al 105 reported that immortal human NSCs could differentiate toward astroglial and neuronal lineage, but not oligodendrocytes in the ischemic brain. Thus, it appears that the injured brain microenvironment does not favor engraftment and regeneration of the transplanted cells.…”
Section: Animal Models Of Other Sct For Hiementioning
confidence: 99%
“…Lee et al 104 reported that the majority of the donor cells remained undifferentiated or became astroglia, with only about 5% and 4% differentiation into neurons and oligodendrocytes, respectively. In an adult ischemic brain injury model, under the condition of immunosuppression either transiently or throughout the experiment, Nodari et al 105 reported that immortal human NSCs could differentiate toward astroglial and neuronal lineage, but not oligodendrocytes in the ischemic brain. Thus, it appears that the injured brain microenvironment does not favor engraftment and regeneration of the transplanted cells.…”
Section: Animal Models Of Other Sct For Hiementioning
confidence: 99%
“…They possess the potential to differentiate into any cell type in the central nervous system (CNS) (although NSCs derived from adult tissues show a more limited differentiation capacity [19]). The integration ability and prospective therapeutic efficacy of human neural stem cells (hNSC) has been demonstrated in rodent models of neurological diseases [20][21][22][23]. Apart from regenerating lost neuronal cells, NSCs can also improve the functional outcomes of rats through auxiliary mechanisms, such as neurotrophism [24][25][26] and immunosuppression [27][28][29].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…Interesting, functional recovery by NSC transplantation was mostly reached through alternative mechanisms rather than cell replacement (Pluchino et al 2005). These mechanisms include neuroprotection and reduction of host cell death (Chu et al 2004), enhancement of endogenous angiogenesis after stroke (Jiang et al 2005), immunomodulatory effects on inflammatory damage (Pluchino, et al 2005;Rota Nodari et al 2010;Ziv et al 2006a) and scavenging of neurotoxic molecules (Emsley et al 2004). Thus far, cells with stem-like properties have been identified in the mammalian CNS, including that of humans, throughout development and adulthood (Alvarez-Buylla et al 2001;Gage 2000;Temple 2001).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…We already obtained some evidence of hNSCs efficacy and immunogenic tolerance upon transplantation into animal models of neurological disorders (Rota Nodari, et al 2010) such as transient global ischemia, which is a model of vascular dementia and resembles several pathological features of AD. At 3 days from global ischemic injury, hNSC were unilaterally implantated into the corpus callosum or the hippocampal fissure of adult rat brains.…”
Section: Low Immunogenic Potential Of Nscmentioning
confidence: 99%
See 1 more Smart Citation